Propranolol in infantile haemangioma: simplifying pretreatment monitoring (Swiss Medical Weekly, 2014)
BACKGROUND: Infantile haemangiomas (IHs) are very common vascular tumours. Propranolol is at present the first-line treatment for problematic and complicated haemangioma. In accordance with a Swiss protocol, children are monitored for 2 days at the start of the treatment to detect possible side effects of this drug. Our study advocates a simplification of the pretreatment monitoring process. METHODS: All children with a problematic and complicated haemangioma treated with propranolol between September 2009 and September 2012 were included in the study. All patients were hospitalised under constant nurse supervision for 48 hours at the start of the treatment and subjected to cardiac and blood measurements. The dosage of propranolol was 1 mg/kg/day on the first day and 2 mg/kg/day from the second day. Demographic data, clinical features, treatment outcome and complications were analysed. RESULTS: Twenty-nine infants were included in our study. Of these, 86.2% responded immediately to the treatment. There were no severe adverse reactions. Six patients presented transient side effects such as bradycardia, hypotension after the first dose and hypoglycaemia later. No side effects occurred after the second dose. Treatment was never interrupted. CONCLUSION: Propranolol (a β-blocker) is a safe treatment for problematic IH. Side effects may occur after the first dose. A strict 48 hour monitoring in hospital is expensive and may be unnecessary as long as the contraindications for the drug are respected.